Examining The Impact of Various Management Strategies Implemented to Combat Post-Harvest Fungal Rots Infecting Yam, Sweet Potato, And Cocoyam: Mengkaji Dampak Berbagai Strategi Manajemen Yang Diterapkan Untuk Memerangi Penyakit Busuk Jamur Pasca Panen Yang Menginfeksi Yam, Ubi Jalar, Dan Talas - Ndifon, Elias Mjaika (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2025)
Roots and tubers are essential foodstuffs, socio-economic, and industrial raw materials. Yams, cocoyam, and sweet potatoes are often infected before harvest, during harvest, in transit, and in storage by pathogens. Some sub-trials were conducted to devise management strategies against the principal fungal pathogens of these crops using botanical and bio-control agents. These inquiries included controlling isolated pathogens in vitro and in vivo. Six replicated experiments were set up using the completely randomized design.  In vitro, botanicals (i.e. Guieria, Bauhinia, Eucalyptus, Ricinus, and Ixora spp.) controlled Lasidioplodia theobromae resulting in up to 35.0% inhibition with time.  Parkia (100% concentration) and Tamarindus 100% significantly controlled L. theobromae most. Secondly, Trichoderma spp. inhibited L. theobromae in vitro causing up to 40% inhibition. T. virens isolate BGMZ2, T. viride AIBK, T. harmatum ZXGV, and T. harzianum AIBN (in descending order of efficiency) performed significantly (p?0.05) better than the Control. Thirdly, Mancozeb, Carbendazim+Mancozeb, and Mancozeb+Copper(I)Oxide+Metalaxyl controlled L. theobromae causing up to 100% inhibition with time. Application of the best botanicals like Guieria (50% concentration), Bauhinia (50% and 100%), Guieria 100%, and Ixora 100% leaves; Eucalyptus (50% and 100%) and Ricinus 100% resins significantly (p?0.05) reduced rots in vivo. These botanicals effectively controlled L. theobromae, causing up to 100% inhibition in vivo with time. Application of Eucalyptus, Cissus, Thymus, and Tamarindus spp. to control Phytophthora colocaciae, as well as application of Cymbopogon, Guieria, and Bauhinia spp. against Colletotrichum alatae lowered percentage rot compared to the control. These control agents were potent and they are strongly recommended.